Construction of invariant solutions and conservation laws to the ( 2 + 1 ) $(2+1)$ -dimensional integrable coupling of the KdV equation - Ben Gao; Qinglian Yin (Boundary Value Problems, 2020)
Abstract Under investigation in this paper is the ( 2 + 1 ) $(2+1)$ -dimensional integrable coupling of the KdV equation which has applications in wave propagation on the surface of shallow water. Firstly, based on the Lie symmetry method, infinitesimal generators and an optimal system of the obtained symmetries are presented. At the same time, new analytical exact solutions are computed through the tanh method. In addition, based on Ibragimov’s approach, conservation laws are established. In the end, the objective figures of the solutions of the coupling of the KdV equation are performed.